DENTISTS' ROLE IN STRENGTHENING THE NATIONAL DEFENSE SYSTEM - Nora Lelyana (The Republic of Indonesia Defense University, 2022)
National defense is a form of effort to maintain state sovereignty, territorial integrity, and national safety. In Indonesia, the national defense system is used in the form of a universal people's defense system that involves all resources prepared by the government and is carried out in a total, integrated, directed, and sustainable manner. The common people's defense and security system is used in dealing with various threats. Military threats place the Indonesian National Army (TNI) as the main component, while non-military threats place Ministries/Institutions as the main component. This study will identify how dentists can play a role in strengthening the defense system in Indonesia. The method used in this study is a qualitative research method with data collection techniques through literature studies and field observations. The results showed that in strengthening the defense system, dentists had the following roles namely 1) examination and treatment of the dental and oral health of soldiers, when the condition of the teeth is not good, it would interfere with the personnel’s performance in the field; 2) in military operations, dentists also play a role in recording the ante mortem of troops; and 3) in the field of review, plays a very large role in identifying disaster victims, this is because teeth are the only part of the body that has a good level of resistance. Military dentists as one of the professionals in the health sector in Indonesia play an active role in strengthening the national defense system, but the distribution of human resources for health workers is still not evenly distributed throughout Indonesia. There needs an effort to manage dental health personnel so that the rights of every Indonesian citizen in the health sector, especially dental health, can be fulfilled optimally.